Five‐year legacy of wildfire and salvage logging impacts on nutrient runoff and aquatic plant, invertebrate, and fish productivity. Issue 6 (17th February 2014) - Silins, Uldis; Bladon, Kevin D.; Kelly, Erin N.; Esch, Evan; Spence, John R.; Stone, Micheal; Emelko, Monica B.; Boon, Sarah; Wagner, Michael J.; Williams, Chris H. S.; Tichkowsky, Ian
ABSTRACT Ecohydrological linkages between phosphorus (P) production, stream algae, benthic invertebrate, and fish communities were studied for 4 years after severe wildfire in the Rocky Mountains (Alberta, Canada). Mean concentrations of all forms of P (soluble reactive, total dissolved, particulate, and total) were 2 to 13 times greater in burned and post‐fire salvage‐logged streams than in unburned streams (p < 0.001). Post‐disturbance recovery of P was slow with differences in P‐discharge relationships still evident 5 years after the fire (p < 0.001). Coupled P and sediment interactions were likely responsible for slow recovery of P regimes in fire‐disturbed watersheds. P loading was associated with strong ecological responses in stream biota. Annual algal productivity was 5 to 71 times greater in streams within burned watersheds than in reference watersheds and persisted for 5 years after the fire (p < 0.001). Elevated algal production was associated with strong differences in benthic invertebrate community structure, including greater invertebrate densities, biomass, species diversity, and shifts in species composition. Monotonic shifts in invertebrate stable carbon and nitrogen isotope ratios indicated increased consumption of autochthonous food sources and effects on energy pathways for invertebrates from fire‐affected streams. Wildfire‐related changes at lower trophic lead to increases in size (weight and length) and growth rate (weight : age ratios) of cutthroat trout (Oncorhynchus clarki). This cascading series of effects of wildfire on stream productivity (primary production, secondary invertebrate consumers, and fish) may be long‐lived legacies of wildfire because of the slow recovery of P regimes. Copyright © 2014 John Wiley & Sons, Ltd.